EVALUASI PROGRAM LAYANAN OBSTETRI DAN NEONATAL DARURAT DASAR DI SEMARANG INDONESIA - Susanti, Susanti; Setiani, Made Yudhi; Yuniningsih, Tri; Sastrawan, Berry (Jurnal Sosial Humaniora, 2024)
The research is motivated by the ineffectiveness of the implementation of the Basic Emergency Obstetric and Neonatal Services (PONED) program at the Bangetayu Public Health Center in Semarang City. This ineffectiveness is primarily attributed to inhibiting factors such as poor communication, a shortage of human resources, and insufficient facilities and infrastructure. These challenges have adversely affected the quality of healthcare services provided to the community and have hindered the program from achieving its intended goals. This research aimed to evaluate the PONED Program implementation at health centres to determine the factors driving and inhibiting its success. This descriptive and qualitative research was carried out at the Bangetayu Public Health Centre, one of the primary health care centres with Basic Emergency Obstetric and Neonatal Services (PONED) in Semarang City. The purposive sampling method was used to collect data from 15 informants through interviews. Public compliance with the program could be seen from the very high participation of citizens in PONED socialization. Community participation in identifying problems and determining the PONED strategy with stakeholders is not in sync with the activities budgeted in the Regional Revenue and Expenditure Budget as deconcentration funds. Program efficiency in terms of task delegation was quite good, although not optimal. Program effectiveness/relevance was not yet fully effective. This evaluation showed that the authority factor greatly influenced the operation of the three indicators. The authority factor of the City Government of Semarang concerned the application of a merit system and the principle of deconcentration in monitoring, as well as special allocation funds for physical/non-physical infrastructure, including competency improvement. Factors supporting the implementation of the PONED Health Center Program found that there were aspects of stakeholder collaboration that determined the success of the program, in addition to aspects of resources, aspects of implementers' attitudes, and aspects of bureaucratic structure.